Therapeutic Ultrasound and Prostate Cancer - Sundaram, Karthik M.; Chang, Sam S.; Penson, David F.; Arora, Sandeep (Seminars in Interventional Radiology, 2017)
Therapeutic ultrasound approaches including high-intensity focused ultrasound (HIFU) are emerging as popular minimally invasive alternative treatments for localized, low-to-intermediate risk prostate cancer. FDA approval was recently granted for two ultrasound-guided HIFU devices. Clinical trials for devices using MRI guidance are ongoing. The current level of evidence for whole-gland ultrasound ablation suggests that its clinical efficacy and adverse event rates including erectile dysfunction and urinary incontinence are similar to current definitive therapies such as radical prostatectomy and external-beam radiotherapy. Short-term data suggest that more focal therapy could reduce the rates of adverse events.
Keywords: high-intensity focused ultrasound; prostate cancer; therapeutic ultrasound; high-intensity directional ultrasound